Stories For Circle Time And Assembly : Developing Literacy Skills and Classroom Values. - Leicester, Mal (Taylor & Francis Ltd., 2005)
This fun new resource is full of lively stories, poems and songs. It can be dipped into for ideas and activities to encourage active and responsible participation, to stimulate discussion and to enhance literacy skills and citizenship education.